2010
DOI: 10.1177/0269881110379288
|View full text |Cite
|
Sign up to set email alerts
|

The incidence and associated risk factors for sudden unexplained death in psychiatric in-patients in England and Wales

Abstract: Clinical characteristics and risk factors associated with sudden unexplained death (SUD) in the psychiatric population are unclear. Psychiatric in-patients (England, Wales) who met criteria for SUD were identified (1 March 1999-31 December 2005). Cases were matched with controls (in-patients alive on the day a SUD occurred). Data were collected via questionnaires. Some 283 cases of SUD were identified (41 annually), with a rate of 2.33/10,000 mental health admissions (in England). Electrocardiograms were not r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 27 publications
2
12
1
1
Order By: Relevance
“…Although previous research has shown both decreased (Honkola et al., ; Leonard et al., ) and increased incidences (Weeke et al., ; Windfuhr et al., ) of SCD in association with benzodiazepine or antidepressant use, we found that the SCD incidence did not differ between patients in the case and control groups that used flunitrazepam and antidepressants. Therefore, we believe that benzodiazepine and antidepressant use are not direct causes of SCD.…”
Section: Discussioncontrasting
confidence: 86%
“…Although previous research has shown both decreased (Honkola et al., ; Leonard et al., ) and increased incidences (Weeke et al., ; Windfuhr et al., ) of SCD in association with benzodiazepine or antidepressant use, we found that the SCD incidence did not differ between patients in the case and control groups that used flunitrazepam and antidepressants. Therefore, we believe that benzodiazepine and antidepressant use are not direct causes of SCD.…”
Section: Discussioncontrasting
confidence: 86%
“…When coadministered with clozapine, event reporters considered valproic acid a suspect of hypothermia in 4 (15.4%) cases, benzodiazepines were considered suspects in 5 (19.2%) cases, while olanzapine was considered a suspect in 8 (30.7%) cases. Interestingly, the demographics and characteristics within Table 3 fit relatively closely with those depicted in a publication from Windfuhr et al, wherein the incidence of sudden unexplained death (SUD) from antipsychotics was examined [25]. In this paper, the authors found that older male patients were slightly more at risk of SUD (58% vs. 42% female), with other risk factors including clozapine, benzodiazepines, cardiovascular disease, and a diagnosis of dementia [25].…”
Section: Literature Reviewsupporting
confidence: 64%
“…Infrequent monitoring of respiratory rate after midazolam IM could be insufficient to detect swift and erratic onset of respiratory depression. When looking at actual clinical practice after RT, few trusts can demonstrate adherence to their own physical health monitoring requirements (Loynes et al 2013); monitoring may occur in as few as 16% of cases (Choudhury et al 2011), and CPR is not initiated as often as indicated, sometimes due to lack of equipment (Windfuhr et al 2011).…”
Section: Midazolam Immentioning
confidence: 99%